Efektifitas Internet Cognitive Behaviour Therapy (iCBT) untuk Menurunkan Deperesi : Systematic Review: Efektifitas Internet Cognitive Behavior Therapy (iCBT) untuk Menurunkan Deperesi : Systematic Review - Primalova Septiavy Estiadewi (Jurnal Kesehatan Masa Depan, 2022)
Depression is a form of psychological mental disorder that has a negative impact on interpersonal relationships, physical health, and daily functioning. Intervention Internet Cognitive Behavior Therapy (iCBT) can be used to support the treatment of patients with anxiety and depression. This Systematic Review aims to conduct the effectiveness of i-CBT in efforts to reduce depression. The review was carried out following the PRISMA guidelines. We conducted a search of three electronic databases (Scopus, PubMed, and Science Direct Database of Systematic Reviews) with relevant keywords. From 15 journals that were conducted and reviewed, iCBT can reduce depression because iCBT therapy can control a person's mood. iCBT therapy is useful for changing negative thoughts and exploring the abilities and positive things of individuals. iCBT therapy can be accessed wherever the client is. The internet can be accessed either via a personal computer or cellphone. iCBT therapy is more effective, efficient, cheaper, and saves time.